Effects of Various Nitrogen Sources on the Growth and Biochemical Composition of Chlorella sp. - Ating Yuniarti; Muhammad Fakhri; Nasrullah Bai Arifin; Anik Martinah Hariati (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Each species of microalga has a preferable nitrogen source for their optimal growth. The nitrogen sources in the grown media affected the growth rate and biochemical composition of Chlorella FNUB01. (NH2)2CO (urea) was found to be the best alternative nitrogen source for Chlorella FNUB01. For producing 1 g of Chlorella FNUB01, the use of urea reduced the cost of medium by 72.6%. Abstract Chlorella sp. is a potential microalgae species to be produced commercially for feed, growth accelerator, and immuno-modulator in fish and shrimp culture. This study aimed to evaluate the various nitrogen sources on the growth, biomass production, and biochemical composition of Chlorella sp. FNUB01. The nitrogen sources used in this study were urea (NH2)2CO, potassium nitrate (KNO3), and ammonium nitrate (NH4NO3). Sodium nitrate (NaNO3) was used as a control as it is a part of the commercial medium BG-11. Generally, the sources of nitrogen in the media affected the growth and chemical composition of Chlorella sp. FNUB01. This green microalga grew better in the urea-containing medium which accounted for 1.5 times the concentration of that cultured in BG-11 (40 x106 cells. mL-1). Meanwhile, this microalgae species experienced the lowest growth when cultured in NH4NO3-containing medium. The biomass productivity of Chlorella sp. FNUB01 cultured in urea (0.93 g.L-1) was comparable to those grown with NaNO3 as the N source. A similar pattern was recorded for protein, chlorophyll, and carotenoid content as these biochemical contents were affected by N availability in the medium. Urea was an alternative low-cost N source for the culture of Chlorella sp. FNUB01. Replacement of NaNO3 with urea could reduce the cost of the medium by 72.6%.